An improved searching method for retrieving local knowledge information - Wong, Poh Lee; Osman, Mohd Azam; Masron, Tarmiji; Talib, Abdullah Zawawi (2016)
Local knowledge information has been widely available for years. These information mainly resides in the form of paper or media which are mainly stored in archives for researchers. When a user tries to retrieve these information, a thorough search has to be done manually to locate specific search query from a user.A lot of these data are not stored digitally and mostly recordered in unstructured form due to the complexity of the data collection.Besides, the implementation of a search method for locating specific information is difficult due to the unstructured form of the data.In this paper, an improved search method which combines the search by selection and search by keywords methods is proposed for retrieving data which can be applied to both structured and unstructured data.The results of the search can be represented in the form of text and graphical charts. The case study presented in this paper is limited to the local knowledge information collected in several states in Malaysia.